(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Textile industry, the oldest industry of India occupies aplace of significance both in providing employment opportunities and in itsproduction and its export potential. This being the situation, it is necessaryto examine the government stand in this regard. The attitude of the government will vitally influence the variousactivities of this industry. Hence, an attempt is made in this paper to reviewthe various government policies with regard to Handloom industry.